Upaya Identifikasi Dini Penyakit Kardiometabolik melalui Skrining Kadar Trigliserida pada Masyarakat Gereja Asisi, Jakarta - Ruslim, Welly Hartono; Santoso, Alexander Halim; Gunaidi, Farell Christian; Putra, Feri Yanto; Kristianto, Angeline Florencia Grace (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
High blood triglyceride levels indicate impaired fat metabolism and can trigger atherosclerosis, making hypertriglyceridemia a major risk factor for cardiovascular disease (CVD), metabolic syndrome, and acute pancreatitis. The productive-age population often experiences overnutrition due to unhealthy diets and low physical activity, increasing fat and triglyceride accumulation. Stress may also elevate triglyceride levels, necessitating early screening. The Community Service Program (PKM) at Assisi Church aimed to raise awareness of early dyslipidemia detection through triglyceride screening using Point-of-Care Testing (POCT) and educational counseling. Among 76 participants, 39 (57.35%) had high triglyceride levels, while 29 (42.65%) were normal. These findings highlight the importance of regular check-ups and continuous education to reduce cardiometabolic risks and promote healthier lifestyles.